Global variation in human tooth crown and root morphology - anthropological and forensic applications - 1 - Scott, G. Richard (Henry Stewart Talks, 2018)
The importance of teeth in anthropology, Dental morphology, Nonmetric traits with strong genetic basis, Traits showing patterned geographic variation on world scale